Urbanization, Economic Inequality, and the Direction of Social Development in the Digital Age - Luis Armando Sabarofek; Achmad Nurmandi; Muhammad Younus (Universitas Pendidikan Ganesha, 2025)
This study aims to analyse how urbanisation and digital transformation processes affect economic inequality and the direction of inclusive social development. Using a qualitative approach based on a systematic literature review, this study reviews Scopus-indexed articles through the PRISMA approach and thematic analysis using NVivo 12 Plus. The results show that digitalisation in its early stages tends to widen income gaps, but in the long term, it can promote socio-economic integration through technology diffusion and increased human resource capacity. Indonesia dominates scientific publications on this topic, indicating the contextual urgency of addressing the challenges of urbanisation and inequality in the digital age. This study emphasises the importance of social development policies oriented towards digital inclusion and strengthening the capacity of local governments in managing sustainable urban transformation. The research recommendations are directed towards the development of digital literacy programmes, expansion of technological infrastructure, and increased cross-border academic collaboration to enrich social development studies in the digital era.